Longitudinal effect of nocturnal R-R intervals changes on cardiovascular outcome in a community-based cohort - Abdulghani Sankari; Laurel Anne Ravelo; Scott Maresh; Nawar Aljundi; Bander Alsabri; Serene Fawaz; Mulham Hamdon; Ghazwan Al-kubaisi; Erika Hagen; M Safwan Badr; Paul Peppard (BMJ Open)
Rationale Sleep-disordered breathing (SDB) is strongly linked to adverse cardiovascular outcomes (cardiovascular diseases (CVD)). Whether heart rate changes measured by nocturnal R-R interval (RRI) dips (RRI dip index (RRDI)) adversely affect the CVD outcomes is unknown.Objectives To test whether nocturnal RRDI predicts CVD incidence and mortality in the Wisconsin Sleep Cohort study (WSCS), independent of the known effects of SDB on beat-to-beat variability.Methods The study analysed electrocardiograph obtained from polysomnography study to assess the nocturnal total RRDI (the number of RRI dips divided by the total recording time) and sleep RRDI (the number of RRI dips divided by total sleep time). A composite CVD risk as a function of total and sleep RRDI was estimated by Cox proportional hazards in the WSCS.Results The study sample consisted of 569 participants from the WSCS with no prior CVD at baseline were followed up for up to 15 years. Nocturnal total RRDI (10-unit change) was associated with composite CVD event(s) (HR, 1.24 per 10-unit increment in RRDI (95% CI 1.10 to 1.39), p<0.001). After adjusting for demographic factors (age 58±8 years old; 53% male; and body mass index 31±7 kg/m2), and apnoea–hypopnoea index (AHI 4%), individuals with highest total nocturnal RRDI category (≥28 vs<15 dips/hour) had a significant HR for increased incidence of CVD and mortality of 7.4(95% CI 1.97 to 27.7), p=0.003). Sleep RRDI was significantly associated with new-onset CVD event(s) (HR, 1.21 per 10-unit increment in RRDI (95% CI 1.09 to 1.35), p<0.001) which remained significant after adjusting for demographic factors, AHI 4%, hypoxemia and other comorbidities.Conclusion Increased nocturnal RRDI predicts cardiovascular mortality and morbidity, independent of the known effects of SDB on beat-to-beat variability. The frequency of RRDI is higher in men than in women, and is significantly associated with new-onset CVD event(s) in men but not in women.